RELASI HUKUM DENGAN KEKUASAAN: MELIHAT HUKUM DALAM PERSPEKTIF REALITASRELASI HUKUM DENGAN KEKUASAAN: MELIHAT HUKUM DALAM PERSPEKTIF REALITAS - FX. Adji Samekto (Faculty of Law, Universitas Jenderal Soedirman, 2013)
Autonomous law reflects enforceability of modern legal system which is promoting the achievement of formal justice and has biased value on the weak, the poor and the marginalized. Limitations of autonomous law further encourages the birth of responsive law, legal typology which reflects an effort to the substantive justice. Discourse about responsive law actually extremely close to the idea of progressive law offers by Satjipto Rahardjo. In the context of this progressive law indeed we are invited to think out of the box of autonomous law way of thinking. Thinking about out of the box here is that we are not constrained by the way of thinking only in modern legal systems - which reflect autonomous law - and consider that it is the most correct way of thinking, as proven autonomous law in practice of modern legal system is only able to realize the formal justice. Meaning contained in these progressive laws can explain the typology meaning of responsive law. Based on analysis study, the application of legal typology of repressive law, autonomous law and responsive law to the community can be carried out by the authorities at the same time depending on that typology of society.Key words: repressive law, autonomous law, responsive law, progressive law, law and authority